2018
DOI: 10.3390/ijerph15081789
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Methylphenidate and Atomoxetine on Heart Rate and Systolic Blood Pressure in Young People and Adults with Attention-Deficit Hyperactivity Disorder (ADHD): Systematic Review, Meta-Analysis, and Meta-Regression

Abstract: Objectives: This meta-analysis aims to study the effects of atomoxetine and methylphenidate on heart rate (HR), systolic blood pressure (SBP), and a number of adverse cardiac events on patients receiving treatment for attention-deficit hyperactive disorder (ADHD) in comparison to placebo and between atomoxetine and methylphenidate. Methods: We searched the following databases: PubMed, EMBASE, and ScienceDirect. Meta-analysis was performed on studies that examined the relationships between methylphenidate or at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
62
1
16

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(81 citation statements)
references
References 59 publications
(68 reference statements)
2
62
1
16
Order By: Relevance
“…No consistent increased risks were found for MI, stroke, heart failure, or hypertension. These data, on the whole, are consistent with a recent metaanalysis of methylphenidate, atomoxetine, and/or placebo in controlled trials that showed a pre-post exposure elevation of systolic blood pressure and heart rate in children and adolescents, but no increase of serious cardiac adverse events [10]. In general, these more minor cardiovascular effects during treatment with ADHD medications are thought to be manageable, although should not be underestimated [37].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…No consistent increased risks were found for MI, stroke, heart failure, or hypertension. These data, on the whole, are consistent with a recent metaanalysis of methylphenidate, atomoxetine, and/or placebo in controlled trials that showed a pre-post exposure elevation of systolic blood pressure and heart rate in children and adolescents, but no increase of serious cardiac adverse events [10]. In general, these more minor cardiovascular effects during treatment with ADHD medications are thought to be manageable, although should not be underestimated [37].…”
Section: Discussionsupporting
confidence: 87%
“…In general, these more minor cardiovascular effects during treatment with ADHD medications are thought to be manageable, although should not be underestimated [37]. For consistency with abovementioned previous systematic reviews of ADHD medications on SCV events [13,14] as well as blood pressure and heart rate [9,10], we did not include guanfacine and clonidine as exposures in our analyses. However, given that these medications have been more Logistic regression for ASD adjustment set 1 is without CHF or PAD, else model cannot converge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This idea is probably counteracted by a central sympatholytic action through activation of α-2 adrenoreceptors, which is similar to "clonidine-like" effect (34). A recent study suggests that children and adolescents treated with atomoxetine were characterized by a significant increase in heart rate and systolic blood pressure rather than subjects treated with methylphenidate (35). Atomoxetine should not be used in children or adolescents with known serious structural cardiac abnormalities, cardiomyopathy, and serious heart rhythm abnormalities, or other se rious cardiac problems (36).…”
Section: Treatment Of Adhd Symptomsmentioning
confidence: 99%
“…6 Contudo, o uso de MPH tem suscitado preocupações com o potencial desenvolvimento de tiques, alteração do perfil de sono ou efeitos no sistema cardiovascular. 7 A ATX é um fármaco não estimulante, que está licenciado para o tratamento da PHDA desde novembro de 2002. 8 Trata-se de um inibidor seletivo da recaptação pré-sináptica de noradrenalina no córtex pré-frontal, originando um aumento da transmissão noradrenérgica, importante para a atenção, aprendizagem, memória e resposta adaptativa.…”
Section: Introductionunclassified